Improved overall survival in an anti-PD-L1 treated cohort of newly diagnosed glioblastoma patients is associated with distinct immune, mutation, and gut microbiome features: a single arm prospective phase I/II trial - Shiao-Pei Weathers; Xiqi Li; Haifeng Zhu; Ashish V. Damania; Mark Knafl; Brian McKinley; Heather Lin; Rebecca A. Harrison; Nazanin K. Majd; Barbara J. O’Brien; Marta Penas-Prado; Monica Loghin; et al. (Nature Communications)
Abstract This phase I/II trial aims to evaluate the efficacy of concurrent atezolizumab with radiation therapy and temozolomide (TMZ) followed by adjuvant atezolizumab and TMZ in newly diagnosed glioblastoma (GBM) patients and to identify pre-treatment correlates with outcome (N = 60). Trial number: NCT03174197. The primary outcome was overall survival (OS) whereas secondary outcomes were retrospective global–omics analyses to identify pre-treatment immune and genetic tumor features that correlated with survival. Concurrent use of atezolizumab with radiation and TMZ demonstrated OS in line with published trials for newly diagnosed GBM. Tumor genomic (WES and/or targeted NGS panel), transcriptomic (RNAseq) and tissue microenvironment imaging, as well as fecal metagenomic sequencing were conducted. Gene set enrichment analysis of tumors identified multiple immune-based transcriptomic programs to distinguish patients with longer versus shorter survival (p ≤ 0.01). GBM immune enrichment was highly associated with the pre-treatment tumor mesenchymal subtype and patient gastrointestinal bacterial taxa profile.